KONSEP BIDAH DAN PANDANGAN KEBANGSAAN MAJELIS TAFSIR ALQURAN (MTA) - Subkhan Ridlo (Jurnal SMART (Studi Masyarakat, Religi, dan Tradisi), 2018)
The education and da’wah movement carried out by the Majelis Tafsir Alquran (MTA) Surakarta particularly and in Indonesia generally is very dynamic. Since its establishment in 1972 by Abdullah Thufail, now the number of MTA branches in Indonesia has reached more than 427 branches. The MTA education and missionary movement carries the idea of purification with the aim of eradicating superstition, heresy and philosophy. This article aims to reveal the concept of heresy and nationalism in the view of MTA. The study was conducted with a qualitative approach through text studies and interviews with MTA figures. The findings of this study indicate that MTA’s view of the concept of bidah (heresy) is textualist, where teachings that are not based on the Qur’an and hadith are heretics and each case that is propagated in religious affairs is heresy. This understanding has the potential to be intolerant towards local cultures such as salvation traditions and talents that are popular in the community. Nevertheless, MTA has a positive view of national concepts. MTA accepts the obligation to respect state symbols such as flags, Bhineka Tunggal Ika, and reject terrorist violence